Meningkatkan Disiplin Belajar Melalui Konsep Diri Siswa - Anwaroti, Ismatul; Humaisi, Syafiq (Institut Agama Islam Negeri Ponorogo, 2020)
ABSTRACTDiscipline is important in life to achieve success. However, the importance of the role of discipline in life is rarely paid attention, the results of observations of researchers in class VII I SMPN 2 Ponorogo show a lack of student discipline when learning is carried out, so the learning process becomes less effective. This is due to the low self-concept of students, they are not fully aware of their role as students. Self-concept can affect a person's behavior, because behavior is closely related to self-understanding. The test of this study was to determine the level of influence of self-concept on the learning discipline of grade VII students at SMPN 2 Ponorogo for the 2019/2020 academic year. The method used in this research is quantitative regression. The population in this study amounted to 286 students, with a cluster sampling technique of 32 students. The results showed that self-concept had an influence on learning discipline based on tcount of 4.114 and ttable 1.699 (then tcount> ttable), with a determination level of 34.7%. Self-concept and learning discipline have a positive relationship, where if a student's self-concept (awareness) is high, then the student's learning discipline is also good, and vice versa if the student's self-concept is low, then the student is less disciplined in learning.ABSTRAKDisiplin menjadi hal yang penting dalam sebuah kehidupan untuk mencapai kesuksesan. Namun, pentingnya peranan disiplin dalam kehidupan jarang diperhatian, hasil observasi peneliti di kelas VII I SMPN 2 Ponorogo menunjukkan kurangnya disiplin siswa saat pembelajaran dilaksanakan, sehingga proses pembelajaran menjadi kurang efektif. Hal ini disebabkan rendahnya konsep diri yang dimiliki siswa, mereka kurang maksimal perannya sebagai pelajar. Konsep diri bisa berpengaruh pada tingkah laku seseorang, karena tingkah laku berkaitan erat dengan pemahaman diri. Tujian dari penelitian ini adalah untuk mengetahui tingkat pengaruh konsep diri terhadap disiplin belajar siswa kelas VII di SMPN 2 Ponorogo Tahun Pelajaran 2019/2020. Metode yang digunakan dalam penelitian ini adalah kuantitatif yang bersifat regresi. Populasi dalam penelitian ini berjumlah 286 siswa, dengan teknik pengambilan sampel cluster sampling yang berjumlah 32 siswa. Hasil penelitian menunjukkan konsep diri memiliki pengaruh terhadap disiplin belajar berdasarkan thitung sebesar 4,114 dan ttabel 1,699 (maka thitung > ttabel), dengan kadar determinasi 34,7%. Konsep diri dan disiplin belajar memiliki hubungan positif, dimana konsep diri (kesadaran) seorang siswa tinggi, maka disiplin belajar siswa juga baik, dan sebaliknya jika konsep diri siswa rendah, maka siswa kurang disiplin dalam belajar.